Beyond 'the choice to drink' in a UK guideline on FASD: the precautionary principle, pregnancy surveillance, and the managed woman. (17th February 2022) - Lee, Ellie; Bristow, Jennie; Arkell, Rachel; Murphy, Clare
Abstract : In many countries, official guidance promotes alcohol abstinence to women during, and also before, pregnancy, on the basis of concern about Foetal Alcohol Spectrum Disorder (FASD). Guidance has moved away from reference to a 'choice to drink', claiming absence of evidence about safety of even 'low level' drinking as a justification. Scholarship drawing on sociologies of risk and uncertainty has drawn attention to problems with precautionary thinking in this area of policy making, including for women's autonomy. We build on these insights to assess a more recent type of UK guidance. This is directed not to women advising them to abstain, but instead it is about women, and tasks health professionals with managing the risk pregnant women's behaviour is deemed to present. Using qualitative discourse analysis, we assess one such example, developed in Scotland, called SIGN 156. We contextualise SIGN 156 first through discussion of the relevant literature, making particular use of Ruhl's considerations of the meaning of risk and the social conditioning of choice, and second through an account of developments in UK Government advice in recent years. We show that SIGN 156 builds on a policy context where a precautionary approach is explicit, but we furthermore detail how this approach innovates the guidance and practice field. SIGN 156 expands the meaning of risk and uncertainty and so justifies 'routine' monitoring and screening, generating the case for an expanded form of surveillance of pregnant women. We conclude with a critical commentary on the implications of this case for analyses of risk and uncertainty, and power.